Analisis Kualitas Layanan Penyerapan Aspirasi Anggota DPR RI Dengan Pendekatan Quality Function Deployment (QFD) - Rizal Sarifuddin (Universitas Serang Raya, 2017)
Public satisfaction can be achieved if the government apparatus directly involved in the service, can understand and appreciate and wish to perform excellent service. This study aims to identify the level of public satisfaction with the performance of Members of the House of Representatives Commission III, to determine the priority of expectations or public desires on the quality of service absorption aspirations of members of Parliament with Servqual method and improve the quality of absorption services by QFD method. This study, using questionnaires, interviews, and observations in data collection. Research respondents are citizens who have filed complaints totaling 100 people. The survey results are processed by using validity and reliability test, analysis of Importance-Performance Analyze (IPA), Servqual, and QFD. The results showed that the community was not satisfied with the performance of members of the House of Representatives with a gap of 0.84. The priority of improvement based on the IPA diagram is the level of professionalism in solving aspirations, the level of responsibility for the expectation of society aspirations, the level of fairness in the aspiration settlement, the level of aspiration service speed, the accuracy of responding to aspirations according to the problem, the timeliness of completing aspirations and the level of responsiveness to resolve aspirations. Increasing the quality of absorption services by QFD method can be done by increasing commitment, discipline, skilled human resources, coordination and synergy and policy improvement that is more concerned with the interests of the community.